Population structure in wintering Dippers Cinclus c. cinclus in northern Lapland 2002—2005 - Tyrén, Håkan; Gustafsson, Hans (Ornis Svecica, 2005)
During the winter seasons October—April 2002—2005, we caught Dippers in the Tjautjas river (67°22'N, 20°49'E), northern Lapland. The age and sex structure was monitored and the territory activities were observed. The number of females was significantly higher than the number of males, a result opposite to our assumption that males should be most common because they are dominant over females. The age distribution between juveniles and adults fluctuated strongly between the years and did not differ significantly from the one found among more than 3,600 wintering birds ringed all over Fenno-Scandia. The Dippers were more mobile than we expected. Unringed Dippers appeared in the stream during the whole winter season, and some individuals disappeared. They shifted spots frequently during winter and interactions were uncommon. Some Dippers also returned to the stream after a few weeks’ absence. Our interpretation is that the Dippers in the Tjautjas river do not defend territories in the strict sense but instead use overlapping homeranges that may involve also other rivers in the area.